PROSESI KHITBAH DI INDONESIA PERSPEKTIF LOCAL WISDOM DAN QAIDAH FIQH - Mohammad Alfin Sulihkhodin (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
In an initial process leading to marital ties is identical to the procession of the sermon as the delivery a serious will to get married. Where in general, the family of men first conveyed their intentions to the women. The implementation of sermon is considered important in order to avoid a regret in the future, considering the divorce rate is pretty much happening lately in Indonesia. This research was conducted in literature study, based on consideration of the provisions of the sermon in view of the local wisdom and qaidah fiqh. The procession of sermons in Indonesia as long as they dont conflict with the principles of fiqh and are of good value, the law is good and highly recommended to be implemented.